HX575: established biosimilarity in the treatment of renal anemia and 10 years of clinical experience - Dellanna F; Goldsmith D; Krendyukov A; Seidl A; Höbel N; Combe C (Dove Medical Press, 2017)
Frank Dellanna,1 David Goldsmith,2 Andriy Krendyukov,3 Andreas Seidl,4 Nadja Höbel,5 Christian Combe6,7 1MVZ Davita Rhein-Ruhr, Düsseldorf, Germany; 2Division of Nephrology, Guy’s and St Thomas’ Hospitals, London, UK; 3Hematology/Nephrology, Hexal AG, Holzkirchen, 4Technical Development Biosimilars, Hexal AG, Oberhaching, 5Biostatistics Medical Affairs/Late Phase, Hexal AG, Holzkirchen, Germany; 6Service de Néphrologie Transplantation Dialyse Aphérèse, Centre Hospitalier Universitaire de Bordeaux, 7Université Bordeaux, INSERM 1026, Bordeaux, France Abstract: Erythropoiesis-stimulating agents, such as recombinant human erythropoietin, are commonly used for the treatment of anemia in patients with chronic kidney disease (CKD). In 2007, HX575 (Binocrit®) became the first biosimilar epoetin alfa to be approved by the European Medicines Agency (EMA). The decision to approve a biosimilar is based on the totality of evidence obtained in a comprehensive comparability exercise that involves extensive analytical characterization, nonclinical studies and clinical studies. The development process for HX575 included extensive analytical characterization and comparison with the reference epoetin alfa. This was followed by a clinical development program, comprising Phase I pharmacokinetic/pharmacodynamic studies to show bioequivalence to the reference medicine and a confirmatory Phase III study to demonstrate therapeutic effectiveness in anemia related to CKD. In addition to the comparability exercises, extensive clinical experience over the last decade also confirms that HX575 provides an effective treatment for CKD-related anemia, with a favorable safety profile. Growing clinical experience with EMA-approved biosimilars, including HX575, should offer additional reassurance to health care professionals and patients that these agents are as effective and well tolerated as others in the therapeutic class. Keywords: Binocrit, HX575, anemia, chronic kidney disease, biosimilars